(untitled) (Global Journal of Management and Business Research, 2016)
The development of SMEs is considered as one of vital determinants of the growth of Ethiopian economy, and for secure equitable distribution of the benefits of the economic growth. However, SMEs in the country are leveled as not performing well and falling short of yielding the much anticipated contribution for the growth of the economy as they are expected. This study is conducted to analyze financial distress level of SMEs in Wolaita Zone and indentify those factors affecting their financial health. In this study 30 firms form three sectors are selected as samples selecting ten samples from each of manufacturing, service and trade sector using purposive sampling method. Accordingly, the results of Altman’s Zeta Score Model analysis indicate that three of the ten selected firms in the service sectors are found to be financially distressed, but none of the sampled SMEs in the sector are below the bankruptcy point. In manufacturing sector, one of the ten selected SMEs is found with the Zeta score of below the bankruptcy line and all of the rest of the sampled SMEs are found to be under financial distress though their Zeta score is above the bankruptcy point.